Mechanical Behavior of Concrete Beams with HDPE Plastic Waste as Partial Fine Aggregates Replacement - Nasruddin; Mushar, Pratiwi; Imriyanti; Zulkarnain (Civil Engineering Journal, 2025)
This study is related to using HDPE plastic bag waste applied to building structural components, specifically concrete beams. An innovation utilizes HDPE plastic waste not in shredded form but by taking advantage of the rigid physical properties of HDPE plastic waste after it is burned, crushed, and sieved to the size of sand to be used as a partial replacement (substitution) for fine aggregate (sand). The type of research conducted is experimental quantitative research to determine the flexural capacity of concrete beams made from HDPE plastic bag waste as a partial replacement for fine aggregates using the normal flexural strength testing method with two-point loading. The test specimens prepared were concrete beams with dimensions of 15 × 15 cm cross-section and 65 cm in length, with varying amounts of HDPE plastic bag waste replacement: 0.00% (normal concrete), 0.50%, 0.70%, and 0.90% of the weight of the sand. The concrete beam specimens were cured using a wet curing method and tested at 14 and 28 days of age. The results showed that at 14 days, the concrete beam specimens with variations of 0.00%, 0.50%, 0.70%, and 0.90% achieved flexural strengths of 3.16, 3.35, 2.91, and 2.97 MPa, respectively. Meanwhile, at 28 days, the specimens with variations of 0.00%, 0.50%, 0.70%, and 0.90% reached flexural strengths of 3.39, 3.95, 3.06, and 3.07 MPa, respectively. The highest flexural strength was achieved by the concrete beam specimen with a 0.50% substitution variation, both at 14 and 28 days, with values of 3.35 and 3.95 MPa, respectively, exceeding the flexural strength of the beam without HDPE plastic waste substitution (0.00%).